Nitrogen and potassium in biomass accumulation in two species of white Spotted Arum - Trejo-Téllez, Libia Iris; Torres-Flores, Nadia Issaí; Tejeda-Sartorius, Olga; Trejo-Téllez, Brenda I.; Ramírez-Martínez, Maribel; Gómez-Merino, Fernando Carlos (Revista Mexicana de Ciencias Agrícolas, 2018)
We evaluated the effect of three nitrogen doses (0.5, 1.5 and 2.5 g plant-1) applied in the vegetative phase and three doses of potassium (4, 6 and 8 g plant-1) applied in the reproductive phase on dry biomass organs (commercial f lower consistent of spathe and spadix, leaves, f lower scapes and rhizomes) of two species of white spotted arum (Zantedeschia albomaculata (hook) Baill. cv. Captain Murano and Z. elliotiana (Watson) Engl. cv. Solar Flare). The experiment was conducted in a greenhouse using as substrate a mixture of tezontle 3 mm/perlite (60/40, v/v). Differential responses were observed in the fertilization treatments between species. The species Z. albomaculata was more sensitive to fertilization, given that it significantly increased the dry biomass of commercial f lowers and leaves with higher doses of N and K supplied. Regardless of the dose of K provided on the reproductive phase, the largest weight of rhizome biomass was recorded in plants treated with the low dose of N in the vegetative phase. According to these results, the N and K fertilization by phenological stages differentially affect the production of dry biomass on the Zantedeschia gender.
Keywords: Zantechia albomaculata; Zantedeschia elliotiana; dry biomass